2008
DOI: 10.1177/1466424008092230
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of dietary and general lifestyle advice among women with polycystic ovarian syndrome

Abstract: In spite of the fact that weight loss and weight maintenance are absolutely vital in the treatment of PCOS, our study has shown that the support given to PCOS patients to help reduce and control their weight is inadequate and needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 9 publications
7
40
1
1
Order By: Relevance
“…The current study suggests that women with PCOS may be more active than previously reported, with 74% self reporting that they did at least 30 min of moderate intensity activity per day, compared with Humphreys and Costarelli (2008), who reported that only 41% of women with PCOS reported undertaking moderate intensity exercise at least once per week. Additionally the Department of Health (2004) has reported that only 24% of women in the general population are sufficiently active to gain any health benefit, the higher rate of activity reported by the current study cohort may be explained by the reported benefits of physical activity improving some of their PCOS symptoms (Jeanes et al, 2009).…”
Section: Recommendation For Weight Management For Overweight Women Wicontrasting
confidence: 48%
See 1 more Smart Citation
“…The current study suggests that women with PCOS may be more active than previously reported, with 74% self reporting that they did at least 30 min of moderate intensity activity per day, compared with Humphreys and Costarelli (2008), who reported that only 41% of women with PCOS reported undertaking moderate intensity exercise at least once per week. Additionally the Department of Health (2004) has reported that only 24% of women in the general population are sufficiently active to gain any health benefit, the higher rate of activity reported by the current study cohort may be explained by the reported benefits of physical activity improving some of their PCOS symptoms (Jeanes et al, 2009).…”
Section: Recommendation For Weight Management For Overweight Women Wicontrasting
confidence: 48%
“…Key sources of dietary information for women with PCOS have been reported as the internet and books (Avery and BraunackMayer, 2007;Humphreys and Costarelli, 2008;Jeanes et al, 2009). It is of concern that many of these sources are unregulated; there are currently no official UK dietary guidelines available for healthcare professionals advising women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, overweight and obese women compared to women with normal BMI (18.5 to 24.9) had lower quality of life. Weight loss is absolutely vital in the treatment of PCOS but the support given to PCOS patients to help reduce their weight is not adequate and more measures are needed for improvement in this area (26).…”
Section: Discussionmentioning
confidence: 99%
“…Behavior therapy is emphasized for weight loss as well as weight maintenance and control. However, despite the great impact of weight loss on PCOS treatment, the support given to PCOS patients to reduce and control their weight is inadequate and needs to be improved [49].…”
Section: Lifestyle Modification In Obese Women With Pcosmentioning
confidence: 99%